2021
DOI: 10.1007/s12520-021-01464-4
|View full text |Cite
|
Sign up to set email alerts
|

Rediscovering the largest kiln site in the middle Yangtze River Valley: insights into Qingbai and grey-greenish ware production at Husi kiln site based on bulk chemical analysis

Abstract: This paper presents new data from the Husi kiln site, Hubei Province, China, where the unusual size calls into question the primacy of Jingdezhen in porcelain production in medieval China. With its over 180 kilns, the site rivals Jingdezhen in size, yet it has found no mention in textual accounts. The wares produced at Husi include Qingbai and grey-greenish ware of the Tang and the Song periods (seventh to thirteenth century AD). This paper presents compositional data obtained using LA-ICP-MS on samples from f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…With the introduction of more elemental techniques into archaeological research, the tracing of burial ceramics and export ceramics can be based on the unique geochemical composition of pottery artefacts combined with factor analysis of various chemical composition to determine their possible provenance [4][5][6][7]. Many studies [3,[8][9][10][11] in the past have successfully aided in the tracing of ceramic products from burials or exports by employing both main elements and REE components. Xu et al [9] used REE components to trace the geochemical characteristics of Qingbai ware from the shipwreck in the Java Sea, revealing that the majority of the Qingbai ware originated from various kilns in the Fujian region.…”
Section: Introductionmentioning
confidence: 99%
“…With the introduction of more elemental techniques into archaeological research, the tracing of burial ceramics and export ceramics can be based on the unique geochemical composition of pottery artefacts combined with factor analysis of various chemical composition to determine their possible provenance [4][5][6][7]. Many studies [3,[8][9][10][11] in the past have successfully aided in the tracing of ceramic products from burials or exports by employing both main elements and REE components. Xu et al [9] used REE components to trace the geochemical characteristics of Qingbai ware from the shipwreck in the Java Sea, revealing that the majority of the Qingbai ware originated from various kilns in the Fujian region.…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al (2012) used principal and REE components to trace the ceramics excavated from the Xicun region and found that Jingdezhen products unearthed from the Xicun area in Guangdong region due to the comparison of peculiar geological characteristics. Li et al (2021) used REE components to successfully distinguish the Qingbai ware excavated from the Husi kiln from other kilns. These ndings support the use of primary chemical and geochemical composition comparisons in tracing ceramic artefacts excavated from burials and shipwrecks.…”
Section: Introductionmentioning
confidence: 99%
“…With the introduction of more chemical techniques into archaeological research, the tracing of burial ceramics and export ceramics can be based on the unique geochemical composition of pottery artefacts combined with factor analysis of principal components to determine their possible provenance [4][5][6][7]. Many studies [3,[8][9][10][11] in the past have successfully aided in the tracing of ceramic products from burials or exports by employing both main elements and REE components. Xu et al (2019) used REE components to trace the geochemical characteristics of Qingbai ware from the shipwreck in the Java Sea, revealing that the majority of the Qingbai ware originated from various kilns in the Fujian region.…”
Section: Introductionmentioning
confidence: 99%
“…The traditional approach has been to conduct typo-chronological studies to explore the origin and date of the ceramics that have no clear provenance (Bishop et al, 1982; Gehres & Querré, 2018). More recently, scholars have been using a combination of typo-chronological methods with chemical fingerprinting to determine the geographical provenance of ceramics (Tochilin et al, 2012; Eiselt et al, 2019; Li et al, 2021). However, the provenance of the Ge ware is difficult to establish as such items have never been found in any archaeological excavation.…”
Section: Introductionmentioning
confidence: 99%